Survey of Academic Ability and Organizational Experience of Alumni Relationship Waiting Physical Education Graduate - Hartono, Mugiyo (Universitas Negeri Semarang (Unnes), 2018)
The purpose of this study is to find out how the academic ability and experience of organizing alumni in relation to the waiting period graduated Physical Education (PE)Â Universitas Negeri Semarang.Survey research with quantitative and qualitative approach has research variable of academic ability, organizational experience, and waiting period of graduates, using as many as 41 samples of graduate of PEÂ last 5 years. Employment status is dominated by school teachers and lecturers in universities of 68.29%. The last level of education is 75.61% with S1 degree of PE and 24.39% with S2 degree. As an undergraduate student actively participate in student activities most of the Ext Sports by 75%. Student activities that followed have a very supportive benefit in the current work of 56.10%. In addition to active student activities there are also 26.68% of students who are active activities outside the campus community organizations. Graduation period of less than 6 months is 75.61%. As many as 58.54% of alumni still survive in the first job. The first place to work in private institutions is 51.22% mainly as teachers. Engaged entrepreneurs at 21.95%. Compliance in the field of work with Pei is 70.73 very appropriate. 65.85% of PE graduates receive salary when they first start working, less than Rp 1,900,000 per month.The conclusion in this research is that the waiting period is less than 6 months in getting a job, strongly supported by the level of academic ability of graduates who have the above criteria both, and experience of organizing a broad graduate.